Song Ci (1186–1249), "Father of World Legal Medicine": History, Science, and Forensic Culture in Contemporary China. Issue 2 (1st June 2017) - Asen, Daniel
Abstract : Song Ci (1186–1249) was an official of the Southern Song Dynasty best known for authoring the Collected Writings on the Washing Away of Wrongs ( Xiyuan jilu ), a work often hailed as the world's first systematic treatise on forensic medicine. While biographical details about his life were known in local history writings during the late imperial period, Song had garnered relatively little attention among those who handled forensic examinations, despite the fact that his work had impacted Chinese forensic practices for centuries. In modern times, by contrast, Song has been praised by historians and forensic professionals and viewed as a founding figure of the modern forensic sciences in China and, in the boldest claims, across the globe. Song has also become the subject of historical novels, television shows, and other popular media. This article examines the ways in which the historical image and meanings of Song Ci have been negotiated in China over the Republican period (1912–49) and after the founding of the People's Republic of China in 1949. It argues that a confluence of modern developments—new concepts of national and world history, the successful implementation of legal medicine in China, and the global popularity of forensics-themed popular culture—has given new meaning and importance to this thirteenth-century figure under the new conditions of the twentieth and early twenty-first centuries.